Penentuan Komoditas Unggulan Subsektor Tanaman Pangan Menggunakan Metode Location Quotient (LQ) dan Fuzzy Analytical Hirarchy Process (FAHP) - Resi, Edmund Ridwanto Alfian; Pangaribuan, Rapmaida Megawaty; Guntur, Robertus Dole; Ginting, Keristina Br (Universitas Negeri Gorontalo, 2024)
This research aims to determine the leading commodities of the food crop subsector in Malaka Regency using the Location Quotient (LQ) and Fuzzy Analytical Hierarchy Process (FAHP) methods. The LQ method is used to identify commodities that have comparative advantages in this region. The results of the LQ calculation show that rice and corn are the base commodities in Malaka Regency because they are the most common in three sub-districts. Rice is the base commodity in the sub-districts of West Malaka (2.14), Central Malaka (2.24), and Weliman (1.70), while corn is the base commodity in the sub-districts of Kobalima (1.21), Wewiku (1.48), and Rinhat (1.26). The FAHP method is applied to integrate various assessment criteria in determining the priority of leading commodities. The results of the FAHP analysis show that the leading commodity in the food crop subsector in Malaka Regency is rice, with a weight value of 0.246 as the top priority, followed by corn, with a weight value of 0.198. The criterion that becomes the top priority in determining leading commodities is the availability of facilities and infrastructure, with a weight value of 0.327. Based on the research results, the combination of the LQ and FAHP methods provides more accurate results in determining leading commodities.